Effect of selected pesticides on Survivality of Exserohilum Longirostratum, A Bioherbicide for Itchgrass - Mohammad Hailmi, Sajili; Jugah, Kadir; Nik Fadzlina, Nik Ahmad; Gooi, Poh Soon (2017)
Four commercial formulations of herbicides and four fungicides were evaluated for their toxic effects on germination of Exserohilum longirostratum. At the recommended rates, one of the herbicides recommended for grassy weed control was compatible with E. longirostratum. E. longirostratum conidia germination was not affected by Paraquat but was totally inhibited by Glufosinate, Glyphosate and Fenoxyaprop-p-ethyl. At lower concentrations, most herbicides were less toxic except Rumpas. The fungicide Benlate at recommended rate has no effect on E. longirostratum. Score and Topper reduced germination more than 50% at recommended rate and growth was distorted. Spore germination was totally inhibited at all concentrations with Dithane. Based on high germination and appresorium development, Sapol and Tween 20 is suitable as carrier for this fungus. Paraquat and Bentazone can be used with E. longirostratum either with tank mixing or as split applications but at concentration less than the recommended rate.